UJI METABOLIT SEKUNDER Trichoderma sp. SEBAGAI ANTIMIKROBIA PATOGEN TANAMAN Pseudomonas solanacearum SECARA In Vitro - Mahmudah Hamawi (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2015)
Trichoderma sp. are highly potential for secondary metabolite production, which have antibiotic effect such as viridin and trikomidin. Viridin and trikomidin has ability to inhibit the growth of the fungus. The secondary metabolite of Trichoderma sp. are essential for developing sustainable agriculture. Aim of this study is to knowing the ability of Trichoderma sp. secondary metabolite to inhibit the growth of bacteria, Pseudomonas solanacearum under in vitro condition. The results showing that: 1) Trichoderma sp. secondary metabolite has ability as growth inhibitor of P. Solanacearum, 2) There were differences effect between inducted and uninducted treatments, 3) the detain effect of inducted was 13, 45 % and un inducted treatment was higher, as 35,98 %.